Dye-Sensitized Core/Active Shell Upconversion Nanoparticles for Optogenetics and Bioimaging Applications - Wu, Xiang; Zhang, Yuanwei; Takle, Kendra; Bilsel, Osman; Li, Zhanjun; Lee, Hyungseok; Zhang, Zijiao; Li, Dongsheng; Fan, Wei; Duan, Chunying; Chan, Emory M; Lois, Carlos; et al. (ACS nano, 2016)
Near-infrared (NIR) dye-sensitized upconversion nanoparticles (UCNPs) can broaden the absorption range and boost upconversion efficiency of UCNPs. Here, we achieved significantly enhanced upconversion luminescence in dye-sensitized core/active shell UCNPs via the doping of ytterbium ions (Yb3+) in the UCNP shell, which bridged the energy transfer from the dye to the UCNP core. As a result, we synergized the two most practical upconversion booster effectors (dye-sensitizing and core/shell enhancement) to amplify upconversion efficiency. We demonstrated two biomedical applications using these UCNPs. By using dye-sensitized core/active shell UCNP embedded poly(methyl methacrylate) polymer implantable systems, we successfully shifted the optogenetic neuron excitation window to a biocompatible and deep tissue penetrable 800 nm wavelength. Furthermore, UCNPs were water-solubilized with Pluronic F127 with high upconversion efficiency and can be imaged in a mouse model.